Do Youngsters Reflect the ‘Fake or Real’ Identity, Personality, and Emotion on Facebook? - Wahyuni, Sri; Isam, Hishamudin; Alber, Alber; Asnawi, Asnawi; Etfita, Fauzul (Makassar State University, 2023)
Abstract: The sophisticated technology has the potential to integrate with social media. Hence, online social sites become a medium for youngsters’ tendency to express their appearance, identity, and narcissism. Consequently, the current study aimed to investigate the reflection of fake or real identity, personality, and emotion of Indonesian teenagers used on social media Facebook. To attain the objective of the study, qualitative descriptive was used as a research design. The data was obtained from youngsters’ posts on Facebook in the range of 2018-2019. The instrument used in gathering the data was Virtual Advertising Operations (VOA). The total data was 1473 posts. In analyzing the data that have been classified based on the three categorizations, we employed AntConc application. The findings show that youngsters express their fake personality, identity, and emotion through Facebook features in terms of style theme with several subthemes followed by spectrums and issues. On the other hand, it could be inferred that youngsters show their identity, personality, and emotion on social media Facebook based on their level of relationship. Further, future research directions on the identity, personality, and emotion of Indonesian youngsters on Facebook are discussed. Keywords: Emotion, Facebook, Identity, Personality, Youngster